Chemical composition and potential commercial values of rambutan (Nephelium lappaceum L.) seed: A review / Nur Hanani Mohd Nizar and Nurul Azlin Tokiman - Mohd Nizar, Nur Hanani; Tokiman, Nurul Azlin (2021)
Rambutan (Nephelium lappaceum L.) seed, which contributes up to 20% of its total fruit weight always being discarded as waste but many recent studies have been done to explore the potential of its commercial value. Rambutan seed has a considerable amount of fat that is beneficial for industrial application. In this review, we summarized the information about the nutritional content, lipid extraction method, anti-nutritional compound, reduction techniques for anti-nutritional compounds and the potential commercial values of rambutan seed. Soxhlet extraction is the common method for lipid extraction either using hexane or petroleum ether as the solvent. The pre-treatment and extraction conditions as well as the moisture content of the rambutan seed could affect the fat yield. In addition, rambutan seed contains considerable amount of beneficial nutrients including carbohydrate (22.18 - 64.19%), protein (8 – 16.21%), fat (6.01- 39.09%), fibre (0.30 – 29%), moisture (2.67- 15.30%) and ash (1.06 – 2.4%). On the contrary, the presence of anti-nutritional compounds in the rambutan seed has contributed to its bitterness and toxicity. These include tannins, saponins and phenolic contents which can be reduced through fermentation, roasting or maceration techniques. Findings show that rambutan seed is highly potential as functional foods and further research can be carried out to extend the utilisation of rambutan seeds. The objectives of this review are to synthesise the research findings on the chemical composition and potential commercial values of rambutan (Nephelium lappaceum L.) seed.